Pendampingan Penguatan Kapasitas Kepala Sekolah Dalam Pelaksanaan Supervisi Akademik Kepada Guru PKG PJOK Gorontalo - Aries, Nur Sakinah; Amri, Muhammad Faisal Lutfi; Hidayat, Joni Taufik; Isnanto, Juni (Jambura Arena Pengabdian, 2025)
School principals play a strategic role in improving the quality of education through the implementation of effective academic supervision. However, in Gorontalo, many principals still lack a deep understanding and technical skills in carrying out supervisory functions, particularly toward PJOK (Physical Education) teachers. This mentoring program aimed to strengthen the capacity of school principals in designing and implementing structured academic supervision that has a tangible impact on teacher performance. The activities involved training sessions, workshops, supervision simulations, and two days of on-site mentoring held at SMP Negeri 1 Limboto, Gorontalo Regency, involving 15 PJOK teachers from various schools across the province. The results indicated a significant improvement in principals' ability to develop academic supervision programs, provide constructive feedback, and identify teacher needs in instructional practices. Over 80% of participants reported enhanced supervision quality based on established indicators, and PJOK teachers demonstrated a better understanding of active learning methods. In conclusion, the mentoring activities proved effective in improving school principals’ competence in academic supervision and contributed positively to the quality of PJOK learning in Gorontalo.